Inhibition of indoleamine 2, 3-dioxygenase activity accelerates skin wound healing. (June 2015) - Ito, Hiroyasu; Ando, Tatsuya; Ogiso, Hideyuki; Arioka, Yuko; Saito, Kuniaki; Seishima, Mitsuru
Abstract: Skin wound healing is a complex process involving several stages that include inflammation, proliferation, and remodeling. In the inflammatory phase, pro-inflammatory cytokines and chemokines are induced at the wound site and, they contribute to the development of wound healing. These cytokines also induce indoleamine 2, 3-dioxygenase (IDO1) activity; this is the rate-limiting and first enzyme in thel -tryptophan (TRP)-l -kynurenine (KYN) pathway. This study examined the effect of IDO1 on the process of skin wound healing. The expression of the Ido1 mRNA was enhanced after creating a wound in wild-type (WT) mice. TRP concentration was simultaneously reduced at the wound site. The rate of wound healing in IDO1 knockout (IDO-KO) mice was significantly higher than that in WT mice. 1-Methyl-dl -tryptophan (1-MT), a potent inhibitor of IDO1, increased the rate of wound healing in WT mice. The administration of TRP accelerated wound healing in vivo and in an in vitro experimental model, whereas the rate of wound healing was not affected by the administration of KYN. The present study identifies the role of IDO1 in skin wound healing, and indicates that the local administration of 1-MT or TRP may provide an effective strategy for accelerating wound healing.